2019
DOI: 10.1111/cpr.12581
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation‐mediated activation of cancer/testis antigen KK‐LC‐1 facilitates hepatocellular carcinoma progression through activating the Notch1/Hes1 signalling

Abstract: Objectives: Kita-Kyushu lung cancer antigen-1 (KK-LC-1) is a cancer/testis antigen reactivated in several human malignancies. So far, the major focus of studies on KK-LC-1 has been on its potential as diagnostic biomarker and immunotherapy target.However, its biological functions and molecular mechanisms in cancer progression remain unknown. Materials and Methods: Expression of KK-LC-1 in HCC was analysed using RT-qPCR,Western blot and immunohistochemistry. The roles of KK-LC-1 on HCC progression were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 51 publications
3
28
2
Order By: Relevance
“…The DLL4-mediated Notch pathway plays a vital role in regulating angiogenesis, especially in regulating embryonic vascular development and tumor angiogenesis[95,96]. The DLL4/Notch pathway in adult vasculature mainly inhibits the activity, migration, and differentiation of endothelial cells, thereby impeding angiogenesis and maintaining vascular stability[97,98]. Generally, vascular endothelial growth factor (VEGF) induces DLL4 production in endothelial cells, which promotes the activation of the Notch signaling pathway, downregulates VEGF3, and promotes endothelial cell sprouting[99].…”
Section: Csc Signaling Pathways and Inhibitorsmentioning
confidence: 99%
“…The DLL4-mediated Notch pathway plays a vital role in regulating angiogenesis, especially in regulating embryonic vascular development and tumor angiogenesis[95,96]. The DLL4/Notch pathway in adult vasculature mainly inhibits the activity, migration, and differentiation of endothelial cells, thereby impeding angiogenesis and maintaining vascular stability[97,98]. Generally, vascular endothelial growth factor (VEGF) induces DLL4 production in endothelial cells, which promotes the activation of the Notch signaling pathway, downregulates VEGF3, and promotes endothelial cell sprouting[99].…”
Section: Csc Signaling Pathways and Inhibitorsmentioning
confidence: 99%
“…Further investigations must be performed to elucidate the potential of targeting SP17 by immunotherapy. CT83 is also expressed in multiple cancers, such as breast, gastric, and lung cancers, and the expression can be upregulated by DNMTis ( 62 67 ). CT83 as a target for TCR-based therapies has shown promising results ( 64 , 68 ), but the potential of the antigen as a target for CAR T-cell therapy remains unexplored.…”
Section: Cancer/testis Antigens As Targets For Car T-cell Therapymentioning
confidence: 99%
“…This results in the release of the Notch intracellular domain (NICD) for translocation into the nucleus to mediate the transcription of pro-survival or anti-apoptosis genes, such as Survivin, B-cell lymphoma-2, or inhibitors of apoptosis proteins (IAPs) [26][27][28] . Increasing evidence demonstrated that inhibition of the activation of the Notch pathway may enhance the efficiency of antitumor agents in HCC cells 29,30 . Therefore, targeting ADAM-17 may be a novel strategy for inhibiting Notch activation and enhancing the sensitivity of HCC cells to antitumor treatment.…”
Section: Introductionmentioning
confidence: 99%